The molecular epidemiology of mycobacterium tuberculosis : role in understanding disease dynamics in high prevalence settings in Southern Africa region - Chihota, Violet (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD)--University of Stellenbosch, 2011.